ANALYSIS OF THE CCD CAMERA ST-4 AND OBSERVATIONS OF PX AND - Andronov, I. L.; Borisov, G. V.; Chinarova, L. L.; Guziy, S. S.; Kolesnikov, S. V.; Mason, P. A. (Одеські астрономічні публікації, 2017)
Analysis of the spectral sensitivity of the CCD camera ST-4 is presented. The half-maximum sensitivity range is 685930 nm. Mean wavelengths λ1 = λ = 796 nm, and λ 2 = (λ -1)-1 = 730 nm are measured. Eclipses of PX And were detected at HJD 48861.3933 and .5393.